Effective Use Of Software Tools In Geometry - Ibragimova Dilnoza Karimbekovna (Global Scientific Publishing, 2023)
The article is devoted to the topic of effective use of software tools in the teaching of geometry, it contains ideas about the effect of using the GeoGebra program on the improvement of students' mastery, and its advantage in describing geometric shapes
Keywords: software tool; education; educational technologies; GeoGebra